ANALYSIS OF THE CULTURE SHOCK PHENOMENA OF CHILDREN IN SOCIAL MEDIA - matondang, abdul rahman (IAIN Padangsidimpuan, 2023)
This study aims to analyze the childfree phenomenon on social media specifically for Tweeters which is associated with Culture Shock. The method used in this research is content analysis by looking at the trend of Childfree issues on Tweeter from March 17-22 2023. The phenomenon analysis uses the Netlytic application which is then analyzed more deeply by looking at the views of MUI, Anthropologists and Communication Experts. The results of this study indicate that the childfree phenomenon on social media can be considered as a form of culture shock due to a shift in social values and norms that were previously considered normal and expected in society. This phenomenon can trigger conflict and polarization on social media, but can also be seen as a form of social and cultural change that is taking place in society. Therefore, it is important for society to accept the social and cultural changes that are taking place and to maintain tolerance towards other people's life choices.